2017
DOI: 10.2340/16501977-2211
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of oral baclofen in the management of spasticity: A rationale for intrathecal baclofen

Abstract: Oral baclofen has long been a mainstay in the management of spasticity. This review looks at the clinical evidence for the efficacy and safety of oral baclofen in patients with spasticity of any origin or severity, to determine whether there is a rationale for the use of intrathecal baclofen. Results suggest that oral baclofen may be effective in many patients with spasticity, regardless of the underlying disease or severity, and that it is at least comparable with other antispasmodic agents. However, adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 54 publications
0
71
0
2
Order By: Relevance
“…The GABA B agonist used for these preclinical studies was R -baclofen, the active enantiomer of baclofen. Racemic baclofen has been extensively used clinically for the treatment of spasticity in cerebral palsy and multiple sclerosis ( Ertzgaard et al , 2017 ; Rizzo et al , 2004 ). The well-known safety profile of the racemic mixture made R -baclofen an attractive clinical candidate for early interventions in neurodevelopmental disorders (the clinical formulation of R -baclofen is also called arbaclofen or STX209).…”
Section: Introductionmentioning
confidence: 99%
“…The GABA B agonist used for these preclinical studies was R -baclofen, the active enantiomer of baclofen. Racemic baclofen has been extensively used clinically for the treatment of spasticity in cerebral palsy and multiple sclerosis ( Ertzgaard et al , 2017 ; Rizzo et al , 2004 ). The well-known safety profile of the racemic mixture made R -baclofen an attractive clinical candidate for early interventions in neurodevelopmental disorders (the clinical formulation of R -baclofen is also called arbaclofen or STX209).…”
Section: Introductionmentioning
confidence: 99%
“… 2 3 Oral antispastics, particularly baclofen, have long been the cornerstone of treatment although they often lead to suboptimal results or cause adverse effects at therapeutic doses. 4 5 While chemodenervation with botulinum neurotoxin type A has become the treatment of choice for focal spasticity, 6 7 it may be inadequate for controlling symptoms over longer periods, particularly in severely affected patients with multifocal/segmental disabling spasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Baclofen is commonly used for treating spastic movement disease ( 49 , 50 ). However, baclofen may help to inhibit hiccups following the insertion of a stent for ESCC, according to a case report ( 51 ), and it was suggested that it may be a useful adjuvant analgesic for decreasing cancer pain ( 52 ).…”
Section: Discussionmentioning
confidence: 99%